3D Porous Hierarchical Nickel–Molybdenum Nitrides Synthesized by RF Plasma as Highly Active and Stable Hydrogen‐Evolution‐Reaction Electrocatalysts. Issue 11 (1st April 2016) - Zhang, Yongqi; Ouyang, Bo; Xu, Jing; Chen, Shi; Rawat, Rajdeep Singh; Fan, Hong Jin
Abstract : Nickel–molybdenum bimetallic nitride dendritic nanofilms are obtained by a fast and environmentally friendly N2 ‐plasma‐activation method. The bimetallic nitride film has a 3D porous dendritic nanostructure and demonstrates outstanding catalytic activity for the hydrogen‐evolution reaction in an alkaline electrolyte.